Insurgency & terrorism from revolution to apocalypse - O'Neill, Bard E. (Manas, 2006)
A systematic, comprehensive and straightforward book that analyze and compares insurgencies and terrorist movements. It covers activity that has since occurred in Afghanistan, India, Pakistan, China, Burma, Iraq, Sudan, the Philippines, Colombia, Nigeria, Saudi Arabia, and elsewhere and highlights the new tactics and weapons used by insurgent groups including al Qaida- and threatened. To suppress terrorism, to undermine terrorism`s ideological support, and to win the war of ideas, a national security expert needs some of the better ideas found in this book.